EDUCATIONAL COPYWRITING AND INTERPERSONAL COMMUNICATION IN ISLAMIC FAMILY LAW COUNSELING: A Digital Media-Based Qualitative Study - Okza Hendrian Wijaya; Dian Marsyah Fabianti Ali; Andre Rahmat Kurniawan Ali; Rahmatullah (Usrotuna: Journal of Islamic Family Law, 2025)
This study examines the role of educational copywriting integrated with interpersonal communication in enhancing Islamic family law literacy within digital media–based counseling, particularly through Instagram. The urgency of the research arises from the widening gap between formal legal language and public comprehension, which often leads to misinterpretation and poor decision-making in family matters such as domestic violence, alimony, financial management, and infidelity. Utilizing a descriptive qualitative method, the study draws on participatory observation, content analysis of Instagram educational posts, and triangulation of primary and secondary data supported by expert validation referencing classical Islamic legal texts and the Compilation of Islamic Law. Findings reveal that educational copywriting, through empathetic narratives, persuasive messages, simplified legal concepts, and relatable storytelling, significantly increases engagement, legal understanding, and emotional connection among followers. Interpersonal communication, manifested through dialogical interactions in comments, direct messages, and story-based Q&A, strengthens two-way knowledge transfer, social support, and the internalization of maqasid syariah values. The integration of both strategies not only enhances digital legal education but also fosters psychosocial empowerment, encourages help-seeking behaviors, and expands access to Islamic family law for younger and vulnerable groups. Contribution: Educational copywriting, when combined with empathetic interpersonal communication, offers an effective, maqasid-oriented framework for strengthening Islamic family law literacy in digital communities. [Penelitian ini mengkaji peran penulisan konten pendidikan yang terintegrasi dengan komunikasi antarpersonal dalam meningkatkan literasi hukum keluarga Islam melalui konseling berbasis media digital, khususnya melalui Instagram. Urgensi penelitian ini muncul akibat kesenjangan yang semakin lebar antara bahasa hukum formal dan pemahaman publik, yang seringkali menyebabkan kesalahpahaman dan pengambilan keputusan yang buruk dalam masalah keluarga seperti kekerasan dalam rumah tangga, nafkah, pengelolaan keuangan, dan perselingkuhan. Menggunakan metode kualitatif deskriptif, penelitian ini memanfaatkan observasi partisipatif, analisis konten posting edukatif di Instagram, dan triangulasi data primer dan sekunder yang didukung oleh validasi ahli dengan merujuk pada teks-teks hukum Islam klasik dan Kompilasi Hukum Islam. Temuan menunjukkan bahwa penulisan konten pendidikan, melalui narasi yang empati, pesan yang persuasif, konsep hukum yang disederhanakan, dan cerita yang relevan, secara signifikan meningkatkan keterlibatan, pemahaman hukum, dan koneksi emosional di antara pengikut. Komunikasi interpersonal, yang diwujudkan melalui interaksi dialogis di kolom komentar, pesan langsung, dan tanya jawab berbasis cerita, memperkuat transfer pengetahuan dua arah, dukungan sosial, dan internalisasi nilai-nilai maqasid syariah. Integrasi kedua strategi ini tidak hanya meningkatkan pendidikan hukum digital tetapi juga mendorong pemberdayaan psikososial, mendorong perilaku mencari bantuan, dan memperluas akses terhadap hukum keluarga Islam bagi kelompok muda dan rentan]. Kontribusi: Penulisan konten pendidikan, ketika digabungkan dengan komunikasi interpersonal yang empati, menawarkan kerangka kerja yang efektif dan berorientasi pada maqasid untuk memperkuat literasi hukum keluarga Islam di komunitas digital].